Under‐Oil Autonomously Regulated Oxygen Microenvironments: A Goldilocks Principle‐Based Approach for Microscale Cell Culture. Issue 10 (4th February 2022) - Li, Chao; Humayun, Mouhita; Walker, Glenn M.; Park, Keon Young; Connors, Bryce; Feng, Jun; Pellitteri Hahn, Molly C.; Scarlett, Cameron O.; Li, Jiayi; Feng, Yanbo; Clark, Ryan L.; Hefti, Hunter; et al.
Abstract: Oxygen levels in vivo are autonomously regulated by a supply–demand balance, which can be altered in disease states. However, the oxygen levels of in vitro cell culture systems, particularly microscale cell culture, are typically dominated by either supply or demand. Further, the oxygen microenvironment in these systems is rarely monitored or reported. Here, a method to establish and dynamically monitor autonomously regulated oxygen microenvironments (AROM) using an oil overlay in an open microscale cell culture system is presented. Using this method, the oxygen microenvironment is dynamically regulated via the supply–demand balance of the system. Numerical simulation and experimental validation of oxygen transport within multi‐liquid‐phase, microscale culture systems involving a variety of cell types, including mammalian, fungal, and bacterial cells are presented. Finally, AROM is applied to establish a coculture between cells with disparate oxygen demands—primary intestinal epithelial cells (oxygen consuming) and Bacteroides uniformis (an anaerobic species prevalent in the human gut). Abstract : Autonomously regulated oxygen microenvironments (AROM), a Goldilocks principle‐based method that recapitulates the oxygen homeostasis and kinetics seen in vivo, is introduced in under‐oil open microfluidic systems (UOMS). Compared to the traditional, operator‐centered oxygen control, AROM allows cells to self‐regulate (i.e., autonomously regulate) and respond to the oxygen microenvironment via a supply–demand balance.